Hidroformilação de substratos monoterpênicos catalisada por complexos de ródio: síntese de produtos de interesse comercial e intermediários para a química fina - Jose Gilberto da Silva (2008)
The hydroformylation of linalool using [Rh(COD)(OAc)]2 as a catalystprecursor in the presence of triphenylphosphine or various diphosphines leads mainly to a mixture of cis and trans isomers of hemiacetal, which formally arise from the intramolecular cyclization of the primarily formed hydroxyl-aldehyde. An unexpected effect of the phosphorous ligands on the reaction rate was observed. With unmodified systems, linalool shows a very low reactivity under the hydroformylation conditions, probably due to the chelation of the substrate on rhodium. The introduction of di)phosphine and the increase in its concentration exerts a great accelerating effect so that under optimized conditions at 40-50oC and 20 atm of CO/H2, a virtually complete conversion of linalool has been achieved in 4-6 hours. A good control of chemo and stereoselectivity was attained through the appropriate choice of reaction variables. Each of two isomers of hemiacetal can be obtained in ca. 95% chemo- and85% stereoselectivity. The rhodium catalyzed hydroformylation of endocyclic monoterpenes, i.e. 2- carene (1), 3-carene (2) and -pinene (3), in the presence of PPh3 or various diphosphines and phosphites has been studied. The unmodified Rh catalyst promotes an intense isomerization of both carenes whose hydroformylation occurs ratherslowly and results in a complex mixture of aldehydes and alcohols. The addition of PPh3, diphosphines or P(OPh)3 in a P/Rh ratio as high as 20 efficiently prevents the isomerization, but the activity for hydroformylation is drastically reduced. On the other hand, the use of a bulky P(O-o-tBuPh)3 ligand both reduces the isomerization and significantly increases the hydroformylation rate. All three sterically crowded olefins 1-3 have been efficiently hydroformylated under relatively mild reaction conditions (80-100oC, 4080 atm) to a main aldehyde (2-formylcarane, 4-formylcarane, and 3-formylpinene, respectively) with good chemo- andregioselectivity and almost 100% stereoselectivity for the trans isomers.Rhodium-catalyzed hydroformylation of - and -terpinene has been studied in the presence of triphenylphosphine. The study revealed that endocyclic dienes can be hydroformylated under mild conditions only if their double bonds are conjugated. An appropriate choice of the reaction conditions allowed to perform readily the hydroformylation of -terpinene, with two major aldehydes being formed in nearly 100% combined selectivity. The results obtained suggest that the coordination of thesubstrate or its insertion on rhodium-hidride bond seems to be the more difficult step of the catalytic cycle. The possibility of fast rearrangement of the 2-olefinic rhodium intermediates into more stable 3-complexes is likely to confer on the conjugated endocyclic double bonds the reactivity towards hydroformylation, whereas nonconjugated ones remain intact under the same conditions.